Reduksi Kadar Oksalat dalam Umbi Porang Menggunakan Variasi Konsentrasi, Suhu dan Lama Perendaman dalam Larutan NaCl dan Akuades - Febrianti, Evril Pramestari; Wardani, Ratih Kusuma (Rekayasa, 2022)
Porang tubers contain compounds that have been widely used in health and industry, namely glucomannan. In addition, porang tubers also contain oxalate compounds that cause itching and burning when consumed directly. Porang tubers that have been cut with a size of 2x2 cm and a thickness of 0.5 cm are soaked using a solution of NaCl and distilled water. Immersion is used to reduce oxalate levels with variations in concentration, temperature and immersion time. Soaking porang tubers in either NaCl or distilled water can reduce oxalate levels. NaCl solution with a concentration of 7% has the highest % decrease in oxalate levels, which is 69.83%. NaCl solution has a better ability to reduce oxalate levels compared to distilled water. The immersion time of porang tubers with NaCl solution for 45 minutes had lower levels of oxalate than using distilled water for 60 minutes, namely 1.0809% (w/w). Porang tubers soaked in NaCl solution at a temperature of 60°C obtained a higher % decrease in oxalate levels compared to distilled water at the same temperature, which was 55.58%.